2022
DOI: 10.3390/ma15155453
|View full text |Cite
|
Sign up to set email alerts
|

Aluminide Diffusion Coatings on IN 718 by Pack Cementation

Abstract: This paper addressed the issues of both direct and indirect synthesis of Ni aluminides by pack cementation (pure Ni and IN 718 superalloy). On the Al-Ni diffusion twosome under pressure, at temperatures below and above the Al melting temperature, the appearance and evolution of diffusion porosity because of the Kirkendall–Frenkel effect manifestation was highlighted. It has been confirmed that, as the temperature rises above the Al melting temperature, the porosity decreases. Nickel-based superalloys, and in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Pack cementation is a process in which metal parts or components are placed in a container filled with a mixture of powdered metal and a chemical activator, typically argon or nitrogen [6]. The container is then sealed and heated to a high temperature, allowing the powdered metal to diffuse onto the surface of the parts, and consequently forming The main aim of this review is to introduce and summarize the recent achievements related to AC deposition by using conventional techniques, including pack cementation (PC), slurry aluminizing and chemical vapor deposition (CVD).…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...mentioning
confidence: 99%
See 3 more Smart Citations
“…Pack cementation is a process in which metal parts or components are placed in a container filled with a mixture of powdered metal and a chemical activator, typically argon or nitrogen [6]. The container is then sealed and heated to a high temperature, allowing the powdered metal to diffuse onto the surface of the parts, and consequently forming The main aim of this review is to introduce and summarize the recent achievements related to AC deposition by using conventional techniques, including pack cementation (PC), slurry aluminizing and chemical vapor deposition (CVD).…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...mentioning
confidence: 99%
“…Pack cementation is a process in which metal parts or components are placed in a container filled with a mixture of powdered metal and a chemical activator, typically argon or nitrogen [6]. The container is then sealed and heated to a high temperature, allowing the powdered metal to diffuse onto the surface of the parts, and consequently forming a hard, wear-resistant coating (Figure 2).…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...mentioning
confidence: 99%
See 2 more Smart Citations
“…Han et al 21 found that the deformation mismatch between the substrate and coating may easily lead to crack initiation and failures under the actual long-term creep process. However, the most accessible literature 22 was based on laboratory studies, which included diverse damage mechanisms under specific loads. Meanwhile, the performance of aluminised-coating under combined oxidation and flow stress, which corresponded to realistic service conditions, was hardly considered in the previous work.…”
Section: Introductionmentioning
confidence: 99%